Measuring the Stability of (Agricultural) Trade Flows in Unstable Times - Thomas Glauben; Tinoush Jamali Jaghdani (Intereconomics, 2025)
The study investigates the challenges to stability in international (agricultural) trade flows, driven by escalating geopolitical and geoeconomic disruption. Against the backdrop of growing protectionist tendencies and the increasing securitisation of international trade, the article addresses the quantification of stability and reliability, synthesises existing empirical evidence and derives implications for the international (agricultural) trade governance and policy.
Keywords: F13; F14; F52; F53; 330